Mutu Beras dan Kandungan Nutrisi Varietas Beras Merah Inpari 24 yang Ditanam dengan Budidaya Organik dan Non-organik - Zahara Mardiah (Seminar Nasional Lahan Suboptimal, 2018)
Mardiah et al, 2019. Grain Quality and Nutrient Content of Red Rice Inpari 24 varieties cultivated in organic and non-organic. pp. 184-192.Organic farming is generally applied for the production of red rice, one of which is Inpari 24. The purpose of this study was to study the effect of organic and non-organic rice cultivation on grain physical quality, milling quality, cooking quality and nutrient content of Inpari 24 varieties grown in organic and non organic. Inpari 24 seeds were obtained from Indonesian Center for Rice Research. Seeds are planted in organic planting locations with international organic certificates (Gapoktan Simpatik, Tasikmalaya). Non-organic crops are carried out in the same district as organic crops. The analysis carried out on the grains produced includes physical quality, milling quality, cooking quality and nutrient content. The results showed that the density of non-organic Inpari 24 grains was higher compared to the density of organic Inpari 24 grain while the other grain physical quality showed no significant difference. The brown rice quality of Inpari 24 organic and non-organic was not significantly different. The head rice of Inpari 24 organic and non-organic was above 85% so that it was included in the premium quality class based on the regulation of the Minister of Agriculture (Permentan) Number 31 / PERMENTAN / PP.130 / 9/2017. The gelatinization temperature of Inpari 24 non-organic was high which was > 74 ºC while the gelatinization temperature of 24 Inpari organic was in the low category which was 55-69 ºC. The gel consistency of Inpari 24 organic and non-organic was not significantly different. The content of iron (Fe), Zinc (Zn), protein and fat of Inpari 24 non-organic brown rice were significantly different from those of Inpari 24 organic brown rice. The content of Fe, Zn and fat were higher in 24 Inpari non-organic brown rice while the protein content was higher in Inpari 24 organic brown rice.